Assessing the Oxidative State of the Skin by Combining Classical Tape Stripping with ORAC Assay - Reem M. Alnemari; Jana Brüßler; Cornelia M. Keck (MDPI AG, 2022)
The antioxidant barrier system of the skin acts as the main defence against environmental pro-oxidants. Impaired skin oxidative state is linked to unhealthy conditions such as skin autoimmune diseases and cancer. Thus, the evaluation of the overall oxidative state of the skin plays a key role in further understanding and prevention of these disorders. This study aims to present a novel ex vivo model to evaluate the skin oxidative state by the measurement of its antioxidant capacity (AOC). For this the ORAC assay was combined with classical tape stripping and infrared densitometry to evaluate the oxidative state of the stratum corneum (SC). Outcomes implied the suitability of the used model to determine the intrinsic antioxidant capacity (iAOC) of the skin. The average iAOC of untreated skin was determined as 140 ± 7.4 µM TE. Skin exposure to UV light for 1 h reduced the iAOC by about 17%, and exposure for 2 h decreased the iAOC by about 30%. Treatment with ascorbic acid (AA) increased the iAOC in a dose-dependent manner and reached an almost two-fold iAOC when 20% AA solution was applied on the skin. The application of coenzyme Q10 resulted in an increase in the iAOC at low doses but decreased the iAOC when doses > 1% were applied on the skin. The results show that the combination of classical tape stripping and ORAC assay is a cost-effective and versatile method to evaluate the skin oxidative state and the pro-oxidate and antioxidative effects of topical skin treatments on the iAOC of the skin. Therefore, the model can be considered to be a valuable tool in skin research.